Anemia in Mexican women: results of two national probabilistic surveys Anemia en mujeres mexicanas: resultados de dos encuestas nacionales probabilísticas - Teresa Shamah-Levy; Salvador Villalpando-Hernández; Armando García-Guerra; Verónica Mundo-Rosas; Fabiola Mejía-Rodríguez; Clara Penélope Domínguez-Islas (Instituto Nacional de Salud Pública, 2009)
OBJECTIVE: To describe the prevalence of anemia in Mexican women and analyze its trends with information from the last two national nutrition surveys. MATERIAL AND METHODS: The prevalence of anemia in women was analyzed. Anemia was adjusted by socioeconomic profile and by potentially explanatory variables. RESULTS: The overall prevalence of anemia for pregnant women was 20.2% (95% CI 15.9, 26.2%) and 15.5% for non-pregnant women (95% CI 14.7, 16.4%). The prevalence of anemia in women decreased from 1999 to 2006 in all socioeconomic profiles. Adolescent women living in the northern and in the southern regions had a greater risk of anemia than those in Mexico City (p= 0.05). Significant risk was found among low socioeconomic level (p< 0.06). Greater parity was a significant risk factor (p< 0.05) for being anemic. CONCLUSIONS: Although anemia in reproductive age women in Mexico decreased, it continues to be a public health problem. OBJETIVO: Describir la prevalencia de anemia en mujeres y analizar su tendencia a través de las dos últimas encuestas nacionales de nutrición. MATERIAL Y MÉTODOS: Se analizó la prevalencia de anemia en mujeres. La prevalencia de anemia se ajustó por perfil socioeconómico y por posibles variables que la expliquen. RESULTADOS: La prevalencia global de anemia fue de 20.2% (IC95% 15.9, 26.2%) para mujeres embarazadas y de 15.5% (IC95% 14.7, 16.4%) para mujeres no embarazadas. La prevalencia de anemia en mujeres disminuyó de 1999 a 2006 en todos los niveles socioeconómicos. Las mujeres adolescentes que viven en las regiones norte y sur tuvieron mayor riesgo de anemia que las que viven en la Ciudad de México (p= 0.05). Se encontró un riesgo significativo asociado con el nivel socioeconómico bajo (p< 0.06). La mayor paridad resultó ser un factor de riesgo significativo (p< 0.05). CONCLUSIONES: Aun cuando la presencia de anemia en mujeres en edad reproductiva en México ha disminuido, continúa siendo un problema de salud pública.